Theoretical approach of teaching lithosphere in junior high school: A critical review of the content and objectives defined by the curriculum of the Ministry of Education - Leontakianakos, G.; Vrachas, C.; Baziotis, G.; Soultati, G.; Fermeli, G. (Bulletin of the Geological Society of Greece, 2013)
The purpose of this study is an attempt to define the lithosphere concept, as described in the textbook “Geology-Geography” of the 1st Grade of junior highschool. Further we investigate whether the objectives of the corresponding chapter are being implemented according to the curriculum of the Ministry of Education. The main research hypothesis concentrates on the very limited cognitive background of the students regarding the lithosphere. It is based on the absence of a wellorganized framework of proportional and gradually increased and specialized flow of knowledge, as suggest the few generalised concepts on the subject of Geography taught on the 5th and 6th grade of the Primary School. According to the Curriculum of the “Geology–Geography” of the Ministry of Education, the lithosphere chapter requires fifteen didactic hours for a sum of nine complexes, mostly cognitive objectives. However, the textbook contains only five didactic hours, an indicator of an asymmetric state of the Curriculum. Our opinion about curriculum content itself, which describes the lithosphere, compared to the strictly scientific definition, is that it represents a simplistic approach and consequently the materialization of the cognitive goals is doubtful.